Analisis Tingkat Literasi Keuangan Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Mataram Dalam Perspektif Keuangan Islam - Yolanda, Arnetta; Atikah, Siti; Lenap, Indria Puspitasari (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to identify the level of Islamic financial literacy among students of the Faculty of Economics and Business at the University of Mataram. University students are an important part of society who are expected to possess sound financial literacy, especially since college is a critical period when they begin to live independently and manage their finances without direct parental supervision. The research employs descriptive statistical methods to provide a general overview of the data obtained from respondents regarding their basic knowledge of Islamic finance. The analysis results show that the average student score is below 60%, indicating a very low level of Islamic financial literacy. Beyond knowledge, the findings also reveal that students lack the attitudes, social motivation, and intention to apply Islamic financial literacy in their daily lives. Their ability to manage finances, such as planning for emergency funds, is also relatively low. This condition highlights the need to improve students’ knowledge and understanding so they can manage their finances wisely in accordance with Islamic principles.